Validation of the Alzheimer’s disease-resemblance atrophy index in classifying and predicting progression in Alzheimer’s disease - He, Qiling; Shi, Lin; Luo, Yishan; Wan, Chao; Malone, Ian B.; Mok, Vincent C. T.; Cole, James H.; Anatürk, Melis (Frontiers in Aging Neuroscience, 2022)
Background: Automated tools for characterizing dementia risk have the potential to aid in the diagnosis, prognosis, and treatment of Alzheimer’s Disease (AD). Here, we examined a novel machine learning-based brain atrophy marker, the AD-resemblance atrophy index (AD-RAI), to assess its test-retest reliability and further validate its use in disease classification and prediction. Methods: Age- and sex-matched 44 probable AD (Age: 69.13  7.13; MMSE: 27-30) and 22 non-demented control (Age: 69.38  7.21; MMSE: 27-30) participants were obtained from the Minimal Interval Resonance Imaging in Alzheimer's Disease (MIRIAD) dataset. After data exclusion, we selected serial T1-weighted images (n = 679) from these participants across over a two-year period, including 179 pairs of scans acquired on the same day and 40 pairs of scans acquired at two-week intervals. All images were automatically processed with AccuBrain® to calculate the AD-RAI. Its same-day repeatability and two-week reproducibility were first assessed. The discriminative performance of AD-RAI was evaluated using the receiver operating characteristic curve, where DeLong’s test was used to evaluate its performance against quantitative medial temporal lobe atrophy (QMTA) and hippocampal volume adjusted by intracranial volume (ICV)-proportions and ICV-residuals methods, respectively (HVR and HRV). Linear mixed-effects modelling was used to investigate longitudinal trajectories of AD-RAI and baseline AD-RAI prediction of cognitive decline. Finally, the longitudinal associations between AD-RAI and MMSE scores were assessed. Results: AD-RAI had excellent same-day repeatability and excellent two-week reproducibility. AD-RAI’s AUC (99.8%; 95%CI = [99.3%, 100%]) was equivalent to that of QMTA (96.8%; 95%CI = [92.9%, 100%]), and better than that of HVR (86.8%; 95%CI = [78.2%, 95.4%]) or HRV (90.3%; 95%CI = [83.0%, 97.6%]). While baseline AD-RAI was significantly higher in the AD group, it did not show detectable changes over 2 years. Baseline AD-RAI was negatively associated with MMSE scores and the rate of the change in MMSE scores over time. A negative longitudinal association was also found between AD-RAI values and the MMSE scores among AD patients. Conclusions: The AD-RAI represents a potential biomarker that may support AD diagnosis and be used to predict the rate of future cognitive decline in AD patients.